THE EFFECT OF TASK-BASED LEARNING METHOD ON STUDENTS’ ACHIEVEMENT IN WRITING PROCEDURE TEXT - Ade Suryani Nasution; Masitowarni Siregar (Universitas Negeri Medan, 2012)
This study aims at investigating the effect of Task-Based Learning Method on students’ achievement in writing a procedure text. This study was experimental in nature. The population of this study was the first year students at SMA Negeri 2 Tanjung Balai. The total number of the population was 280 students in seven classes. There were 60 students chosen as the sample by using random sampling technique. The sample was divided into two groups, namely control group and experimental group. The experimental group was taught by using Task-Based Learning Method and control group was taught without using Task-Based Learning Method. The instrument for collecting the data was a writing test. To obtain test reliability, the writer applied the Pearson Product Formula. The calculation showed that the reliability of the test was 0.90. It was categorized as very high reliability. The data were analyzed by using the t-test formula. The result of the analysis showed that the t-observed value was higher than t-table (2.34>2.00) at the level of significance 0.05 with a freedom degree of 58. It means that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. Based on the findings of this study, it was found that there was a significant effect of Task-Based Learning Method on students’ achievement in writing procedure texts. Key Words: Task-Based Learning, Writing, Procedure Text.